(untitled) (Scientific journal of the Fergana State University, 2023)
The scientific article analyzes the features of the concept of "media text", which is a hyperonym of such terms as journalistic text, advertising text, PR-text. The typology of media text and peculiarities of its functioning in Russian mass media are considered: distribution channels, functional-genre type, institutional type of text, thematic dominance. The differences and peculiarities of television texts, Internet texts, and newspaper texts are analyzed. As examples, the mass media are considered: newspapers, TV channels, radio, Internet media. The relevance of the research topic is determined by the fact that with the advent of the information age, mass communication media have acquired great importance in the life of modern society. The demand for scientific research in this area is increasing every year, since media texts reflect dynamic changes in linguistic reality. When working on the scientific article we used the works of scientists: T.G. Dobrosklonskaya, Y.N. Zasursky, G.Y. Solganik, Y.V. Rozhdestvensky.